Analisis Kitin dari Cangkang Kepiting Rajungan (Portunus pelagicus) - Irma, Wa; Karyani, M. Said; Amarlita, Dhamas M. (Lembaga Intelektual Muda (LIM) Maluku, 2023)
Crab skin is a processing waste that reaches 50-60% by weight intact, with a chitin content of 20-30%. If this waste can be utilized, then in addition to overcoming the problem of water pollution, it will also provide added value to the fisheries processing business. Until now, the use of these wastes is still very limited. Its use includes making petis, shrimp paste, flavor, and as a feed ingredient. This research is about the isolation of chitin from crab shell shells through the stages of demineralization and deproteination. The research method used in this study has 2 stages, namely deproteination with variations in NaOH reagent concentrations of 3.5%, 45.0%, 5 and 6.5%, and demineralization with HCl reagent concentrations of 1 M. Test characteristics of chitin and chitosan isolated results carried out with IR. The results of data analysis showed that the isolation of chitin from crab shells went through several stages, namely two stages of deproteination and demineralization stages. The optimum concentration of NaOH reagents used in the deproteination process is 4.50% with the concentration of protein that can be released in the first test of 18.0467 gr and in the second test of 17.8445 gr. The optimum concentration of HCl reagent used in the demineralization stage is 0.1 N. The optimum incubation time for the chemical deproteinas stage i is 2 hours with chitin levels produced of 32.8320 gr